The tadpole of Melanophryniscus cambaraensis Braun & Braun, 1979 (Anura: Bufonidae) - Bernardo-Silva, Jorge Sebastião; Santos, Raquel Rocha Dos; Both, Camila (Zootaxa, 2010)
The genus Melanophryniscus comprises 24 species, occurring in northern Argentina, southern Bolivia, southern Brazil, Paraguay, and Uruguay (Frost, 2009). The genus belongs to the family Bufonidae; it is probably monophyletic (Graybeal & Cannatella, 1995), and was considered a sister taxon of all other bufonids by Frost et al. (2006). Melanophryniscus cambaraensis was described in 1979 by Braun and Braun, and belongs to the M. tumifrons group (Cruz & Caramaschi, 2003). The species is endemic to the southeastern Araucaria Forest, southern Brazil, with records from Cambará do Sul (type locality; Braun & Braun, 1979), and neighbor areas in the municipality of São Francisco de Paula (Kwet & Di-Bernardo, 1999). The tadpole of M. cambaraensis is undescribed so far. Herein, we describe its external morphology, and compare it briefly with the tadpole of M. orejasmirandai Prigioni and Langone, the only previously described tadpole in the Melanophryniscus tumifrons group.